Menanga Formation as volcanic submarine fan deposit of Woyla Arc in Sumatra, Indonesia - Widiatama Angga Jati; Santy Lauti Dwita; Nahar Rikza Nur Faqih An; Hendrawan Rezki Naufan; Natalia Happy Christin; Ogara Evan Rosyadi; Christi Dea Ananda Gita (MATEC Web of Conferences, 2024)
The Menanga Formation is part of the Woyla terrane, the last large terrane amalgamated formed island of Sumatra. Woyla terrane consist of Cretaceous arc assemblage and relatively lack of research has been done on this formation in Lampung and surrounding areas. This study aims to identify the facies of the Menanga Formation. Research was carried out by making a measured stratigraphic and dividing it into facies and facies associations. The data were taken from two places, in Gunungkasih, Tanggamus and Way Sabu, Pesawaran, Lampung. The results showed that the Menanga Formation has nine facies, there are graded bedding sandstone (F1), loadcast sandstone (F2), parallel lamination coarse sandstone (F3), parallel lamination medium sandstone (F4), parallel bedding fine sandstone (F5), ripple fine sandstone (F6), lamination red sandstone (F7), grey claystone (F8), and parallel lamination red claystone (F9). The Menanga Formation facies were grouped into three facies associations, AF1 consist of F1, F2, F3, F4, and F5 shown channel geometry, fining upward trend, and Bouma classical turbidite deposit, while AF2 consist of monotonous interbedded of F5, F6, and F7 as upper part of the turbidite sequence, while AF3 shown distal facies association (AF3) consist monotonous interbedded of F8, and F9. The stacking pattern shows fining upwards and thining upwards trend interpreted to be channel-levee deposits in the midfan lobe of the submarine fan, while the monotonous of interbedded claystone with thin layers of sandstone in upper part interpreted to be deposited in the outer fan lobe submarine fan. Menanga Formation sandstone consists of lithic graywacke whose grains are dominated by lithic minerals, small amounts of feldspar and minor quartz. The discovery of indicates the relative age this formation ranging from Jurassic to Cretaceous. The discovery of radiolaria Pantanellium sp. indicates the relative age this formation ranging from Jurassic to Cretaceous. The Menanga Formation interpreted to be deposited in submarine fan environment whose sediment with material originates from the Woyla volcanic arc.